2018
DOI: 10.1590/0102-311x00051017
|View full text |Cite
|
Sign up to set email alerts
|

Early-life socioeconomic status and malocclusion in adolescents and young adults in Uruguay

Abstract: This study aims to estimate orthodontic treatment need among 15-24 year-old individuals in Montevideo, Uruguay, and the association of occlusal traits with demographic, clinical and socioeconomic factors, considering a life course approach. A cross-sectional study using data from the First National Oral Health Survey in Uruguay was conducted. A two-stage cluster procedure was used to select a sample of 278 individuals in Montevideo. Household interviews and oral examinations were performed by six dentists. Den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 24 publications
1
9
0
5
Order By: Relevance
“…Comparing results obtained in Quito with findings obtained in Latin American cities, we observed a prevalence of severe or handicapping malocclusion of around 25%, which is similar to studies performed in some Brazilian cities [27–29] or the value observed in the Brazilian Oral Health Survey, conducted in 2010 [30]. Comparing with other regions from Latin America, prevalence value observed in Quito was slightly higher than those observed in Uruguay or Mexico [31, 32]. However, these latter studies were conducted with older persons, what can explain the differences.…”
Section: Discussionsupporting
confidence: 87%
“…Comparing results obtained in Quito with findings obtained in Latin American cities, we observed a prevalence of severe or handicapping malocclusion of around 25%, which is similar to studies performed in some Brazilian cities [27–29] or the value observed in the Brazilian Oral Health Survey, conducted in 2010 [30]. Comparing with other regions from Latin America, prevalence value observed in Quito was slightly higher than those observed in Uruguay or Mexico [31, 32]. However, these latter studies were conducted with older persons, what can explain the differences.…”
Section: Discussionsupporting
confidence: 87%
“…[19] Children belonging to low socioeconomic class in government schools had more number of untreated caries compared with children from private schools which is similar to the study conducted by Schou (1995)[20] and Goettams (2018). [21] It is well known that children from low socio economic background cannot afford the costly dental treatment. The reason could be lack of dental awareness and less affordability to dental care.…”
Section: Discussionmentioning
confidence: 99%
“…Possíveis justificativas para a expressiva taxa de má oclusão encontradas nesse estudo podem estar relacionadas às baixas condições socioeconômicas (Goettems et al, 2018;Rebouças et al, 2017;Teixeira et al, 2016;Silveira et al, 2016) nas quais a maioria dos adolescentes pesquisados estão inseridos e, também, ao baixo grau de escolaridade materna apresentado (Teixeira et al, 2016;Goettems et al, 2018;Rebouças et al, 2017). Development, v. 9, n. 10, e699108403, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i10.8403 Segundo trabalhos realizados por Teixeira et al (2016), as condições socioeconômicas estariam relacionadas às condições bucais.…”
Section: Variáveisunclassified
“…Esses autores relatam que existe uma relação potencial entre o status socioeconômico na primeira infância e a ocorrência de más oclusões em adolescentes. É possível que o percurso socioeconômico determine a exposição a fatores predisponentes à má oclusão, incluindo a adoção de hábitos nocivos, como a sucção digital, uso de chupeta, mamadeira, respiração bucal e onicofagia, e às perdas precoces de elementos dentários pior saúde bucal e menor oportunidade de acesso a medidas preventivas, consultas e tratamentos precoces (Goettems et al, 2018).…”
Section: Variáveisunclassified